Actitudes de los estudiantes y su influencia en el trato de las secretarias de la Facultad de Ciencias Jurídicas, Sociales y de la Educación - Carpio Litardo, Jessica de los Angeles (2022)
The present case study is aimed at determining the influence of the attitudes of the students in the treatment of the secretariats of the Faculty of Legal Sciences and Education. The development of this case study is carried out through descriptive research with the application of the deductive method and the use of the survey as an instrument for collecting information, the same ones that allowed obtaining precise information on the problem presented, the development of the survey was very effective at the time of obtaining information because it clearly guided the obtaining of very relevant and necessary opinions from the respondents. With the information obtained in this case study, he revealed the shortcomings in relation to the problem and proposed possible solutions in relation to these, in order to take self-awareness and self-assessment.